Near-infrared photoelectrochromic device with graphene quantum dot modified WO3 thin film toward fast-response thermal management for self-powered Agrivoltaics - Chang, Ling-Yu; Chang, Ching-Cheng; Rinawati, Mia; Chang, Yu-Hsin; Cheng, Yao-Sheng; Ho, Kuo-Chuan; Chen, Chia-Chin; Lin, Chia-Her; Wang, Chia-Hsin; Yeh, Min-Hsin (Applied energy, 2024)
Agrivoltaic system is the use of land for both photovoltaic energy production through the installation of solar panels and for pastoral and crop cultivation. This work has proposed an idea of introducing a near-infrared photoelectrochromic device (NIR-PECD) into the agrivoltaic system for realizing the self-powered thermal management, revealing the temperature control for a greenhouse without external power supplier to increase the yield of the crops, while reducing the energy consumption for the plant growing. As a commercial and widely used electrochromic material in PECD, WO3 has been reported as a significant and effective material in numerous electrochromic materials. To improve of electrochromic response of WO3 for coloring/bleaching in NIR-PECD, in this study, graphene quantum dot (GQD) was introduced into the WO3 to promote the electrochromic performance. The graphitic sp2 structure and specific functional groups improved the WO3 thin film's electrochromic results by enhancing the response rate and transmittance contrast. The NIR-PECD with GQD/WO3 electrochromic layer showed a significant improvement in response time for bleaching (93.3 s), compared to the case with pristine WO3 one (271 s). The photocoloration efficiency (PhCE) of NIR-PECD was also improved from 55.85 to 96.46 cm2 min−1 W−1 after introducing GQD into the WO3 thin film. Under 1 sun illumination, the colored state and bleached state of NIR-PECD with GQD/WO3 electrochromic layer showed a temperature difference of 8.7 °C. GQD/WO3 thin film maintained approximately 90% of the original transmittance contrast after 1000 cycles of coloring and bleaching, due to the hydrogen bonds formed between functional groups on GQD and WO3. By integrating the Prussian blue (PB) electrochromic electrode, GQD/WO3-PB complementary NIR-PECD can achieve self-powered indoor thermal management by changing the transmittance as an agrivoltaic system. [Display omitted] •GQD was introduced into the WO3 to promote the electrochromic performance.•GQD/WO3 based NIR PECD showed a transmittance contrast of 40% at 1000 nm.•Existence of the hydrogen bonds via GQD enhanced the stability of the WO3 thin film.•NIR-PECD with GQD/WO3 electrochromic layer showed a temperature difference of 8.7 °C.•Complementary PECD for Thermal Management in Agrivoltaics was proposed.